Cover Image. Issue 8 (19th August 2018) - Spartalis, Eleftherios; Spartalis, Michael; Tsilimigras, Diamantis I.; Moris, Demetrios; Garmpis, Nikolaos; Damaskos, Christos; Dimitroulis, Dimitrios; Troupis, Theodore; Tomos, Periklis
Abstract : The cover image, by Eleftherios Spartalis et al., is based on the Clinical Image Extensive or partial first rib resection for thoracic outlet syndrome? The contribution of three‐dimensional imaging to the preoperative planning and the postoperative evaluation, DOI:10.1002/ccr3.1617 .